2021
DOI: 10.1097/bpb.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgical treatment of symptomatic bipartite patella in teenage athletes

Abstract: Bipartite patella affects about 2% of people. Most cases are asymptomatic; however, some develop anterior knee pain during sports. When conservative treatment fails, surgery can be considered. This study reports the outcomes of fragment excision with or without lateral release in teenage athletes with symptomatic bipartite patella. The study was approved by the College of Medicine Institutional Review Board. A retrospective review was performed. Patients were excluded if age >18 or had prior knee surgery. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Distinctive advantages of arthroscopic intervention are minimal access, no damage to the extensor mechanism, assessing the knee for concurrent pathology, extensile denervation for pain relief, quick recovery, and early return to sport. Studies have shown, excision of the accessory fragment resulted in 100% success in returning patients to prior activities, with 91% returning to their respective sports without symptoms and 9% returning with residual symptoms [ 3 , 10 ]. Being an elite player, we offered arthroscopic surgery to our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Distinctive advantages of arthroscopic intervention are minimal access, no damage to the extensor mechanism, assessing the knee for concurrent pathology, extensile denervation for pain relief, quick recovery, and early return to sport. Studies have shown, excision of the accessory fragment resulted in 100% success in returning patients to prior activities, with 91% returning to their respective sports without symptoms and 9% returning with residual symptoms [ 3 , 10 ]. Being an elite player, we offered arthroscopic surgery to our patient.…”
Section: Discussionmentioning
confidence: 99%
“…When conservative treatment fails, surgery can then be considered [ 9 ]. Few studies have reported on the outcomes of operative treatment in the adult population [ 5 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%